2021
DOI: 10.2196/29201
|View full text |Cite
|
Sign up to set email alerts
|

A Smartphone Intervention for People With Serious Mental Illness: Fully Remote Randomized Controlled Trial of CORE

Abstract: Background People with serious mental illness (SMI) have significant unmet mental health needs. Development and testing of digital interventions that can alleviate the suffering of people with SMI is a public health priority. Objective The aim of this study is to conduct a fully remote randomized waitlist-controlled trial of CORE, a smartphone intervention that comprises daily exercises designed to promote reassessment of dysfunctional beliefs in multip… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(59 citation statements)
references
References 61 publications
1
58
0
Order By: Relevance
“…Although, previous studies have shown the effects of GGtude platform interventions remain for at least one month ( e.g. , Aboody et al, 2020 ; Ben-Zeev et al, 2021 ), our results were assessed at 12 days. Future studies would benefit assessing the effects of such intervention over a longer follow up periods.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Although, previous studies have shown the effects of GGtude platform interventions remain for at least one month ( e.g. , Aboody et al, 2020 ; Ben-Zeev et al, 2021 ), our results were assessed at 12 days. Future studies would benefit assessing the effects of such intervention over a longer follow up periods.…”
Section: Discussionmentioning
confidence: 98%
“…Use of mHealth apps has also been shown to be associated with reductions in anxiety, depression, self-harm and negative body image ( e.g. , Ben-Zeev et al, 2021 ; Burns et al, 2011 ; Chandrashekar, 2018 ; Firth et al, 2017a ; Melia et al, 2020 ; Rodgers et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations